the Edukasi Pengenalan, Pencegahan, Dan Deteksi Dini Risiko Penyakit Jantung Pada Wanita Usia Subur sebagai upaya pencegahan stunting Di Desa Motui Kabupaten Konawe Utara - Hikmandayani, Hikmandayani; kartini; Farming; Dewi Mardhani; Siti Aisa (Poltekkes Kemenkes Kendari, 2024)
Cardiovascular disease is still a global threat and is a disease that plays a major role as the number one cause of death worldwide. Data from the World Health Organization (WHO) states that more than 17 million people in the world die from heart and blood vessel disease. Cardiovascular disease also most often attacks the productive age group, so that its mortality causes an economic and social burden on society. Cardiovascular disease starts from simple steps. The Motui village area in North Konawe Regency, Southeast Sulawesi Province, whose population is mostly lower middle class, has low education, socio-demographic factors and unbalanced food consumption habits, this is the determinant of hypertension and heart disease in coastal communities. There is an increase in understanding of women of childbearing age about prevention and early detection of heart disease, on average women of childbearing age have sufficient knowledge (58.00) and after participating in activities it has increased to a good category (90.00)